O PAPEL DO SUJEITO EM UMA ENCICLOPÉDIA ONLINE - Henge, Glácia da Silva (Organon, 2010)
This text seeks to review the notion of subject from the perspective of discourse analysis to investigate the established designation for those who edit the online encyclopedia Wikipedia. For this, other important notions are rescued, such as: image, discoursive place, meaning and memory. Going through the formulations components of the encyclopedia, we can see the slides of meaning and the game of powers between the speeches, been emerging in the subjectivity of speech through an idealization. The Wikipedian would be, then, the correspondent at the plan of designation of an imaginary construction of the figure of an internet user as the one who applies all web resources and who is free to express himself, exchange with other internet users and who is an encyclopedist inside the virtual universe.